2015
DOI: 10.1021/acs.molpharmaceut.5b00635
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Targeting Peptides for Mucosal Delivery in Sheep and Mice

Abstract: In this study we identified and characterized a novel cyclic peptide that facilitates the rapid transportation of conjugated molecules across the epithelial layer of the small intestine. The peptide was initially selected from phage display libraries using a large animal experimental model which employed consecutive in vitro and in vivo panning. The procedure was designed to enrich for peptides that facilitated transcytosis across the intestinal epithelium into the intestinal afferent lymphatic system. A small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Microscopic analysis revealed that the fluorochrome-labeled 13C transporter is taken up while the scrambled control peptide largely remains in the lumen of the large intestine, as already shown previously for the small intestine (4). Uptake is first observed in a subset of epithelial cells that have the morphological features of goblet cells, notably in the small intestine (4), but the conjugate also becomes detectable in mucosal CD11c + cells, which mainly consist of DCs (Figure 3).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Microscopic analysis revealed that the fluorochrome-labeled 13C transporter is taken up while the scrambled control peptide largely remains in the lumen of the large intestine, as already shown previously for the small intestine (4). Uptake is first observed in a subset of epithelial cells that have the morphological features of goblet cells, notably in the small intestine (4), but the conjugate also becomes detectable in mucosal CD11c + cells, which mainly consist of DCs (Figure 3).…”
Section: Discussionsupporting
confidence: 82%
“…The 13C peptide, a nine amino acid long cyclic peptide facilitated mucosal uptake of coupled molecules by, as of yet, unknown mechanisms (4). We here studied the impact of this strategy on vaccination efficacy and tolerance induction in the DO11.10/OVA323-339 peptide (pOVA) model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations